IMPROVING STUDENTS ABILITY ON ENGLISH FOR SPECIFIC PURPOSE (ESP) COURSE THROUGH STAR 7 JUMPS MODEL AT COACH STUDY PROGRAM FKIP- UNRI - Erni Erni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
This classroom action research design was aimed at analysing students failure in learning ESP (English for specific purposes) and finding out its solution. The purpose of this study was to improve the ability of Coach  Study Program students of FKIP UNRI  in learning ESP  through STAR 7 Jumps model and to find out factors that contribute more to the improvement. Total 36  students which consisted of 27 boys and 9 girls involved as the participants of the study. This research was done in two cycles. Designing syllabus, evaluating teaching materials, and compiling teaching materials were also the procedures done in each cycle (Planning, action, observation and reflection). Semi-structured observation sheets and field note was used to identify how lecturer teaching and how learners learning and ESP achievement test was employed to identify students ability. The lecturer applied the seven steps of STAR well and it made the students more active, motivated and interested in learning ESP. Students’ ability in learning ESP was also improved where mean pre-test was 67, mean post-test cycle 1  was 73 and mean post-test cycle 2 was 76.  The most dominant factor that caused the improvement was the teaching materials about match sports topic by which most students were active in problem identification, brainstorming, analyzing and formulating problems, self-study and presentation.